Analysis Of Creative Content On Social Media As Political Communication: A Case Study Of The North Sumatra Regional Elections In 2018-2024 - M. Rio Fani; Yusniah Yusniah (UNIVERSITAS PAKUAN, 2025)
This study aims to analyze the use of creative content on social media as a political communication tool during the North Sumatra Regional Head Election from 2018 to 2024. Using a qualitative descriptive method, this research examines various types of creative content employed by candidates and their campaign teams to attract attention and build public image. Data were collected through documentation studies and observations on social media platforms such as Instagram, Facebook, and Twitter. The findings reveal that creative content, including short videos, memes, and infographics, plays a crucial role in shaping voter perceptions and enhancing digital interactions. This study also uncovers effective political communication strategies through the dynamic and innovative use of social media. The implications of this research can serve as a reference for political candidates and communication practitioners in designing more effective digital campaigns targeted at younger audiences.